Fuzzy-ART based adaptive digital watermarking scheme - Chang, Chip Hong (2009)
In this paper, a novel transform domain digital watermarking scheme that uses visually meaningful binary image as watermark has been developed. The method embeds the watermark information adaptively with localized embedding strength according to the noise sensitivity level of the host image. Fuzzy adaptive resonance theory (Fuzzy-ART) classification is used to identify appropriate locations for watermark insertion and its control parameters add agility to the clustering results to thwart counterfeiting